The political communication style of ridwan kamil in west java spatial news - Alam, Wira Yudha; Marijan, Kacung; Aminah, Siti (Jurnal Studi Komunikasi, 2019)
This research is aimed to understand the political communication style of Ridwan Kamil as the governor of West Java province towards the urban spatial planning in West Java. This research utilises van Dijk's critical discourse analysis method because it is considered to be a clear method in the process of data analysing. Sources of this research will be gathered from spatial planning-related three online news (tempo.co, inilahkoran.com, pikiranrakyat.com) from September 2018 to July 2019. This research discovers that Ridwan Kamil has an equalitarian style, which he able to digest the situation with his two-way communication and idea acceptance.